Coping strategies in the management of traumatic events and cognitive and emotional processing from disclosure - Santos, Carina (2019)
Poster presented at the 3rd International Congress of CiiEM - Research and Innovation in Human and Health Sciences. Monte da Caparica, Portugal, 20-22 June 2018.